ATIVIDADE ANTIOXIDANTE E TEOR DE COMPOSTOS FENÓLICOS E FLAVONOIDES TOTAIS DE Cinnamomum triplinerve (LAURACEAE) - PEZENTI, Letícia; ABEL, Mayara Cristina Neves; FEITOSA, Bruno Henrique; YUNES, Rosinara Virginia Ferreira; SILVA, Ana Francisca Gomes (ANAIS DO ENIC, 2018)
-